High Prevalence of Mitochondrial tRNA A3243G Mutation in Invasive Breast Cancer - Alhomidi, Mohammed A.; Hasan, Qurratullain (Asian Pacific Journal of Cancer Biology, 2021)
Background & Aim: Mitochondria play vital roles in various cellular activities, such as energy production, maintaining the redox balance of the cell, the regulation of cellular proliferation and differentiation, and programmed cell death. Mitochondrial tRNA mutations are associated with many pathological conditions and numerous diseases have been associated with them. Therefore, the objectives of this study were to evaluate the presence and the frequency of mutations in the selected tRNAs in breast cancer patients and to correlate these mutations with the clinicopathological characters. Materials & Methods: The is a cross sectional study, where seventy seven breast tumors and adjacent non-tumorous (normal) tissue samples were analyzed by PCR- RFLP, and direct DNA sequencing. In this study three mt-tRNAs wre selected, two of them are the most important disease associated mt-tRNAs i.e tRNALue (UUR), tRNALys and one of the least pathogenic associated tRNA which is tRNAarg. Statistical analysis was used to determine the relationship between the detected mutations and the clinicopathologhical characters. Results: The tRNAleu (UUR) A3243G mutation occurring at the highly conserved location was detected in 4 samples (5.2%) of both breast cancer and adjacent non-tumorous tissue except one detected only in tumor tissue. Another A8343G mutation was detected in tRNAlys. There was no significant association between these mutations and clinicopathological parameters (P. value > 0.05). Conclusion: The detection of high frequent A3243G mutations in patients with invasive breast cancer suggests role of this mutation in the carcinogenesis. This mutation affects complex I, reduces translation of its core subunits, which can contribute to the impairment of oxidative phosphorylation and increase ROS production, leading to cancer progression.